Research methods for human resource management - Sanders, Karin; Cogin, Julie A.; Bainbridge, Hugh T.J. (2014)
"Since the beginning of the century, there have been calls for the integration of traditional individualistic (micro) and management (macro) paradigms in Human Resource Management studies. In order to understand this so-called 'black box,' the HR field needs research which is more sensitive to institutional and cultural contexts, focusing on formal and informal relationships between employees, supervisors and HR managers and the means by which these organizational participants enable and motivate one another. This book presents advanced quantitative and mixed research methods that can be used to analyze integrated macro and micro paradigms within the field of Human Resource Management. Multi actor, social network and longitudinal research practices, among others, are explored. Readers will gain insight into the advantages and disadvantages of different research methods in order to evaluate which type is most suitable to their research. This book is suitable for both advanced researchers and graduate students"--
Includes bibliographical references and index.
Keywords: Personnel management -- Research; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Management